Effects of sex and genotype in human APOE‐targeted replacement mice on alcohol self‐administration measured with the automated IntelliCage system before and after repeated mild traumatic brain injury. (4th October 2021) - Simmons, Kathryn E.; Healey, Kati L.; Li, Qiang; Moore, Scott D.; Klein, Rebecca C.
Abstract: Background: Few studies have examined the association between APOE genotype and alcohol use. Although some of these studies have reported outcomes associated with a history of drinking, none have examined alcohol‐seeking behavior. In addition, no preclinical studies have examined alcohol use as a function of APOE genotype with or without traumatic brain injury. Methods: Male and female human APOE3‐ and APOE4‐targeted replacement (TR) mice were used to assess voluntary alcohol seeking longitudinally using a 2‐bottle choice paradigm conducted within the automated IntelliCage system prior to and following repeated mild TBI (rmTBI). Following an acquisition phase in which the concentration of ethanol (EtOH) was increased to 12%, a variety of drinking paradigms that included extended alcohol access (EAA1 and EAA2), alcohol deprivation effect (ADE), limited access drinking in the dark (DID), and progressive ratio (PR) were used to assess alcohol‐seeking behavior. Additional behavioral tasks were performed to measure cognitive function and anxiety‐like behavior. Results: All groups readily consumed increasing concentrations of EtOH (4–12%) during the acquisition phase. During the EAA1 period (12% EtOH), there was a significant genotype effect in both males and females for EtOH preference. Following a 3‐week abstinence period, mice received sham or rmTBI resulting in a genotype‐ and sex‐independent main effect of rmTBI on the recovery of righting reflex and a main effect of rmTBI on spontaneous home‐cage activity in females only. Reintroduction of 12% EtOH (EAA2) resulted in a significant effect genotype for alcohol preference in males with APOE4 mice displaying increased preference and motivation for alcohol compared with APOE3 mice independent of TBI while in females, there was a significant genotype × TBI interaction under the ADE and DID paradigms. Finally, there was a main effect of rmTBI on increased risk‐seeking behavior in both sexes, but no effect on spatial learning or cognitive flexibility. Conclusion: These results suggest that sex and APOE genotype play a significant role in alcohol consumption and may subsequently influence long‐term recovery following traumatic brain insults. Abstract : Alcohol preference was measured in the mouse IntelliCage using the drinking in the dark paradigm during the chronic phase of traumatic brain injury in APOE targeted replacement mice. There were significant genotype X sex and genotype X TBI interactions for the average % EtOH preference. This novel study highlights the importance of sex and APOE genotype as significant factors in studying alcohol consumption in the context of TBI.